Draft Genome Sequences of Two Pasteurella multocida Strains Isolated from Buffaloes in India with Hemorrhagic Septicemia Disease - Abrahante, J. E. (American Society for Microbiology, 2014)
Pasteurella multocida serotype B:2 is the causative agent of hemorrhagic septicemia in cattle and buffaloes in Asia. It is an acute fatal disease and is considered one of the most economically important diseases in this region of the world. We present here the draft genome sequences of strains 2213 and 3213 of P. multocida.